Genetic Parameters for Yolk Cholesterol and Transcriptional Evidence Indicate a Role of Lipoprotein Lipase in the Cholesterol Metabolism of the Chinese Wenchang Chicken - Chen, Xingyong; Zhu, Wenjun; Du, Yeye; Liu, Xue; Geng, Zhaoyu (Frontiers in Genetics, 2019)
The yolk cholesterol has been reported to affect egg quality and breeding performance in chickens. However, the genetic parameters and molecular mechanisms regulating yolk cholesterol remain largely unknown. Here, we used the Wenchang chicken, a Chinese indigenous breed with a complete pedigree, as an experimental model, and we examined 24 sire families (24 males and 240 females) and their 362 daughters. First, egg quality and yolk cholesterol content were determined in 40 weeks old chickens of two consecutive generations, and the heritability of these parameters was analyzed using the half-sib correlation method. Among first-generation individuals, the egg weight, egg shape index, shell strength, shell thickness, yolk weight, egg white height, Haugh unit, and cholesterol content were 45.36±4.44 g, 0.81±0.12, 3.07±0.92 kg/cm2, 0.340±0.032 mm, 15.57±1.64 g, 3.36±1.15 mm, 58.70±12.33, and 274.3±36.73 mg/egg, respectively. When these indexes were compared to those of the following generation, no statistically significant difference was detected. Although yolk cholesterol content was not associated with egg quality in females, an increase in yolk cholesterol content was correlated with increased yolk weight and albumin height in sire families (p-value < 0.05). Moreover, the heritability estimates for the yolk cholesterol content were 0.328 and 0.530 in female and sire families, respectively. Therefore, the yolk cholesterol content was more strongly associated with the sire family. Next, chickens with low and high yolk cholesterol contents were selected for follicular membrane collection. Total RNA was extracted from these samples and used as a template for transcriptional sequencing. In total, 375 down- and 578 up-regulated genes were identified by comparing the RNA sequencing data of chickens with high and low yolk cholesterol contents. Furthermore, GO term and KEGG pathway enrichment analyses indicated the involvement of energy metabolism and immune-related pathways in yolk cholesterol deposition. Several genes participating in the regulation of the yolk cholesterol content were located on the sex chromosome Z, among which lipoprotein lipase (LPL) was associated with the PPAR signaling pathway and the GO term cellular component. Collectively, our data suggested that the ovarian steroidogenesis pathway and the down-regulation of LPL played critical roles in the regulation of yolk cholesterol content.